Exploration of antinociceptive, antipyretic and anti-inflammatory activitiesof Curcumin in male rat - Al-Tahan, Fraid (Iraqi Journal of Science, 2024)
Curcumin, one of active ingredients of Curcuma spp. Roxb (Zingiberaceae) isreferred to main medicinal part in this spice. In the present study, the analgesic,antipyretic and anti-inflammatory actions of Curcumin were investigated in malerats. Ninety Albino male rats (110-125g) were used in this study (six animals wereused in each test for Curcumin, aspirin and Pethedine). The effects of curcumin onnociceptive response using writhing, tail flicking and formalin tests in rats wereevaluated. The antipyretic activity in yeast-induced fever and anti-inflammatoryactivity in carrageenin-induced edema in rats were examined. Administration ofcurcumin significantly P<0.05 decreased the number of writhing and stretchinginduced by acetic acid, and suppressed the licking activity of the late phase informalin test in rats. Curcumin had significant decrease P<0.05 effects on yeastinducedfever and carrageenin-induced edema in rats. Furthermore, the ED50 fromLog dose response curve exhibited sequence order potency in formalin test, writhingreflex and tail flick as aspirin > curcumin. Curcumin showed synergistic effectcentrally acting pethidine and peripheral analgesic aspirin. From these results it canbe concluded that curcumin possesses analgesic effect via a different mechanismfrom that of aspirin and pethidine.